Race moderates the association between adult attachment avoidance and the cortisol awakening response among young sexual minority men. (November 2022) - Cook, Stephanie H.; Wood, Erica P.; Chan, Anthea; Rambarran, Shakti; Aguilera, Liz
Abstract: Adult attachment, or the ways in which individuals develop and maintain trusting and loving relationships with peers and romantic partners, has been demonstrated to influence hypothalamic-pituitary-adrenal (HPA) axis functioning among young sexual minority men (YSMM). Theory and preliminary evidence suggest that differences in the lived experiences of White and Black sexual minority young adults may influence the way in which adult attachment influences the HPA-axis functioning. We sought to further this field of inquiry by examining if race moderates the association between adult attachment insecurity (i.e., avoidance and anxiety) and HPA-axis functioning among YSMM. Sixty-three YSMM participated in a 5-day daily diary study in which they completed a baseline survey to assess adult attachment orientation and provided saliva samples 4 times per day over a 5-day period in order to measure cortisol across the day. Three-level hierarchical linear modeling was used to examine the association between adult attachment, the cortisol awakening response (CAR), diurnal cortisol, and the moderating effect of race. We found no main effect of attachment anxiety or avoidance on HPA-axis functioning. However, we found that race moderated the association between adult attachment avoidance and the CAR such that Black YSMM with higher attachment avoidance had a lower CAR as compared to White YSMM. Results suggest that there may be key differences between White and Black YSMM men's lived experiences that should be explored in future research. Highlights: Adult attachment avoidance is associated with the cortisol awakening response (CAR) among young sexual minority men (YSMM). YSMM higher on avoidance had a higher CAR compared to YSMM lower on avoidance. Black YSMM higher on attachment avoidance had a lower CAR as compared to White YSMM.